Cafe Intelegensia: Kewirausahaan Berbasis Kebudayaan dalam Memperkenalkan Budaya Kalimantan Selatan - Muhammad Rivaldi Akbar (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
Cafe Intelegensia is an innovative concept initiated by entrepreneurs who aim to establish a culture-based café that contributes to regional development through community involvement. The café integrates cultural elements as its main attraction, including (1) Madihin performances, (2) a café library, (3) Panting music, (4) stand-up comedy, and (5) traditional Banjar games. These activities are designed not only to entertain visitors but also to introduce, preserve, and promote local culture in a modern setting. This study aims to examine how culture-based entrepreneurship can support the development of South Kalimantan’s cultural identity in the era of globalization, ensuring that younger generations of the Banjar community continue to value and preserve their original traditions while contributing to regional growth. The research method used is descriptive qualitative, employing a literature study approach and conceptual analysis to explore the role of cultural entrepreneurship in community development. The results indicate that Cafe Intelegensia functions not only as an economic driver but also as a space for cultural expression, social interaction, and the promotion of local wisdom in South Kalimantan, thereby strengthening cultural sustainability and community engagement.